Introduction to Management, Advantages of Webinar and Online Lectures in Teaching Basic Theories and Functions of Management (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Webinar is a tool designed to coordinate various events or distance learning online or in the company's corporate network. The use of modern information technologies in this form serves to ensure communication between offices or branches of organizations that are geographically distant from each other.